2021
DOI: 10.18805/ajdfr.dr-208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Lactococcus lactis Isolated from a Fresh Local Cheese of the Western Algerian Steppe “J’ben of Naama”

Abstract: Background: The purpose of the study is to evaluate the diversity of lactococci, lactic bacteria, recovered from “J’ben”, a local cheese made from the milk of the Rembi sheep breed, a product of exploitation in the Algerian steppe regions of Naama.Methods: The bacterial species were isolated from samples of the recovered cheese exploitation and analyzed using genotypic methods. The isolation of bacterial DNA from purified Lactococcus cultures has been established by an amplification of ribosomal DNA 16s using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Any traditional foods reflect a symbiotic relationship between the physical characteristics of the region and the culture of the rural community (Licitra, 2010). The cheeses are classified according to their typicality, derived from the characteristics of their land of origin (Dahou et al, 2021;Delfosse, 2006;Montel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Any traditional foods reflect a symbiotic relationship between the physical characteristics of the region and the culture of the rural community (Licitra, 2010). The cheeses are classified according to their typicality, derived from the characteristics of their land of origin (Dahou et al, 2021;Delfosse, 2006;Montel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…lactis between 12 to 12.5 mm, and 03 strains of Leu.mesenteroides between 17.5 to 22.5 mm, while none of the fifteen tested strains exhibited lipolysis activity in Tributyrin agar medium (Table1). Mechai et al (2014) found that only two strains of the genus Lactococcus isolated from fermented milk and traditional cheese had strong proteolytic activity; however, Dahou et al (2021) found that ten Lactococcus lactis isolated from traditional Algerian cheese "J'ben" had proteolytic activity. Furthermore, another study found similar characteristic in one Lactococcus (Lc.…”
Section: Resultsmentioning
confidence: 99%
“…J'ben is a traditional soft white cheese prepared from non-pasteurised raw milk (sheep, goat, or cow). J'ben is a popular cheese in rural regions due to its unique taste and nutritional properties offered by its indigenous flora (Bousbia et al, 2018;Dahou et al, 2021). Lactic acid bacteria are a group of organisms that are Gram-positive, non-sporulating, cocci, coccobacilli, or rods, catalase negative, and have the common property of producing lactic acid.…”
mentioning
confidence: 99%
“…The total bacterial DNA of selected isolates and reference strains used was checked and extracted using the method developed by BIO-RAD laboratories and adopted by (Cholet, 2006;Gevers et al 2001;Koenraad et al 2008;Dahou et al 2021).…”
Section: Dna Extractionmentioning
confidence: 99%